Integrated ICT Systems Over Sustainable Cloud Environment (International Journal of Innovative Research in Engineering & Management, 2023)
In the traditional education management  systems, records of current or former users are maintained by public or private organizations. And these records are in the institution or ministry that students attend or attended. And these records are maintained conventionally. If a user wants to transfer from one organization to another, the candidate’s records may  transfer along with the organization, but some education  records may remain at school or education department.  Or when they apply for further delegation, the process of  applying and verification of the certificate takes too  much time. In the traditional education management  system, every educational department maintains data  with their own database for keeping the records. Now it  is very difficult to know the complete previous or present record of a student in the different organizations. And if we want to, then we retrieve their entire data from their  concern educational departments, which takes a lot of  time. For better management, there are such software which are  available in the market, but schools or institutions find it  difficult to retrieve the exact information from the system and managing the system with tons of student records,  technical management of the software and the more users  makes the system more complicated. The purpose of this paper is to describe the design of a cloud base digitized academic system for improving current traditional  education system.
Keywords: Digitization; Cloud; Verification; Tracking; Academic records